Kesadahan Air Media Pemeliharaan dan Pengaruhnya Terhadap Kualitas Produk Kepiting Soka - Sunaryo Sunaryo; Ali Djunaedi; Adi Santoso (Jurnal Kelautan Tropis, 2017)
Mangrove crabs (Scylla serrata Forsskål, 1775) is one of the biological resources of the sea, that have economically important value and has been widely cultivated by traditional farmers to meet food needs in both the local and export markets. But the resulting quality of soft shell crab is not optimal. Quality is determined by the hardness of crab carapace after moulting.  Approach to problem solving can be done through the research process of the aquatic organisms to their environment adaptation.This research was aimed to acknowledge the influence of the difference in water softening against time duration the hardening rate of the crabs carapace. This research had done in the area of brackishwater pond in the village of Mojo, Ulujami, Pemalang Regency during 8 months. Animal test used a Mangrove crab (S. serrata Forsskål, 1775), the weight size of 80-150 g, individually kept in plastic boxes (30 x 20 x 25 cm), 15 pieces per m2 density. Research was carried out using case study method. The observation parameters of research was aimed at the water softening and calcium content of rearing water media and body fluids of mangrove crabs, and time duration of carapace hardening. The data obtained from the results of the measurement and calculation of the research parameters of each sampling, include: carapace hardening response due to differences in water softening and calcium content in the rearing media as well as  calcium content in the body fluid of the mangrove crab was analyzed using t-test. Observation on the research results showed that the process of soft shell crab production using rearing media of brackishwater and freshwater, each was respectively difference in the containing value of water softening and calcium content (p < 0.01).   The water softening and calcium content of mangrove crabs as well as the calcium content of body fluid of the mangrove crab to response of time duration the carapace hardening on the mangrove crab after moulting as a whole indicated very significant difference (p < 0.01).  But the results of the statistical analysis of calcium content in the body fluid of mangrove crab with the environmental rearing water media on each individual habitat suggested not significant difference (p ≥ 0.01).  The conclusions of these research, i.e. water softening and calcium content of the rearing water of mangrove crab was the determining factor in the quality of the soft shell crab product. On the occasion research was advised to do optimization of water softening in the rearing crab, so resulting highly quality product of soft shell crab.   Kepiting bakau (Scylla  serrata  Forsskål, 1775) merupakan salah satu sumber daya hayati laut yang mempunyai nilai ekonomis penting dan banyak dibudidayakan oleh petani tradisional untuk memenuhi kebutuhan pangan baik di pasar lokal maupun ekspor. Namun kualitas kepiting soka yang dihasilkan belum optimal. Kualitas kepiting soka sangat ditentukan oleh tingkat kekerasan kulit kepiting setelah moulting. Pendekatan pemecahan masalah ini dapat dilakukan melalui penelitian proses adaptasi organisme perairan terhadap lingkungannya. Penelitian ini bertujuan untuk mengetahui pengaruh perbedaan kesadahan terhadap lama waktu kecepatan pengerasan carapace kepiting. Penelitian dilakukan selama 8 bulan di pertambakan Desa Mojo, Kecamatan Ulujami, Kabupaten Pemalang. Hewan uji yang dipergunakan berupa Kepiting Bakau (S. serrata Forsskål, 1775), berat 80 - 150 g, dipelihara pada bok plastik (30 x 20 x 25 cm) secara seluler, padat penebaran 15 ekor per m2. Penelitian dilakukan dengan menggunakan metode studi kasus. Parameter penelitian ditujukan pada kesadahan dan kandungan kalsium air media pemeliharaan dan cairan tubuh Kepiting Bakau serta lama waktu pengerasan carapace. Data yang didapatkan dari hasil pengukuran dan perhitungan parameter penelitian pada tiap - tiap pengambilan sampel, meliputi: respon pengerasan carapace akibat perbedaan kesadahan dan kandungan kalsium dalam media air pemeliharaan serta kandungan kalsium dalam tubuh kepiting bakau dianalisis dengan menggunakan uji t tes. Hasil pengamatan di dalam penelitian menunjukkan bahwa proses produksi kepiting soka menggunakan media pemeliharaan air tambak dan tawar, masing – masing mengandung nilai kesadahan dan kandungan kalsium yang berbeda (p<0,01).  Kandungan kesadahan dan kalsium air media pemeliharaan Kepiting Bakau pada media air pemeliharaan yang berbeda menunjukkan perbedaan sangat signifikan terhadap respon waktu pengerasan carapace Kepiting Bakau setelah moulting (p<0,01). Namun hasil analisis statistik kandungan kalsium cairan tubuh kepiting bakau dengan lingkungan media air pemeliharaan pada masing – masing habitat menunjukkan tidak adanya perbedaan yang sangat nyata (p≥0,01). Kesimpulan penelitian ini, yaitu kesadahan dan kandungan kalsium air pemeliharaan merupakan faktor penentu kualitas produk kepiting soka. Pada penelitian selanjutnya disarankan untuk mengoptimalkan kesadahan sehingga dihasilkan produk kepiting soka berkualitas tinggi.